Audience Motives and Satisfaction on Accessing Online Tours at 360° Virtual Destinasi Indonesia - Endah Murwani; Rismi Juliadi; Agustinus Rusdianto Berto; Rustono Farady Marta (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2021)
The tourism sector is one of the industries affected by the COVID-19 pandemic. Therefore, the Indonesian Ministry of Tourism and Creative Economy is developing a virtual tour innovation through the